PERANCANGAN SISTEM PENEMBAKAN MENGGUNAKAN MOTOR SERVO MG996R UNTUK AUTONOMOUS ROBOT GUN (ARO-GUN) - Sanjaya, Sukma; Muhtar, Ali; Prasetyawan, Purwono (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
The ever-growing and increasingly sophisticated weapons technology has led countries to continue to develop automated weapons. Since manual control of the movement and position of the weapon is very difficult to obtain a high degree of accuracy, inaccuracies in firing can cause fatalities. In order to minimize errors and inaccuracies in shooting and facilitate military performance in the use of weapons, automatic weapon drives are required. In this study, a product called ARO-GUN was developed to perform target locking and firing using an MG996R servo-type DC motor. This ARO-GUN product is based on testing when locking and firing has an X-axis accuracy of 98.51% and an average error rate of 1.50% and an average Y-axis accuracy of 97.97% and an average error rate of 1.94%. Based on research and testing, it can be inferred that the ARO-GUN product firing system can facilitate military performance in the use of weapons and minimize fatalities due to errors and inaccuracies in firing.